2016
DOI: 10.13005/ojc/320206
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Screening of Subtropical Plants Cultivated in Jeju Island for Cosmetic Ingredients

Abstract: To identify novel cosmetic ingredients from subtropical plants, we screened 21 parts of 12 plant species collected from the Agricultural Research Institute for Climate located in Jeju Island, the southernmost island of the Korean Peninsula. Subtropical plants were investigated for their total polyphenolic content by using the Folin-Ciocalteu reagent with gallic acid as the standard as well as 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS) scavenging activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Notably, in the investigation of Lee et al, R. rugosa (HP. 13) was found to provide a strong DPPH scavenging activity, and another study by Zheng et al also indicated that R. rugosa possessed the most powerful antioxidant potential evaluated by DPPH and ABTS assays among 65 edible flowers (Kim et al 2016;Zheng et al 2018). Moreover, there have been few investigations referring to the antioxidant activities of S. komarovii, A. princeps, and R. rugosa (Carvalho et al 2011;Kim et al 2018;Lee et al 2012;Youwei and Yonghong 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, in the investigation of Lee et al, R. rugosa (HP. 13) was found to provide a strong DPPH scavenging activity, and another study by Zheng et al also indicated that R. rugosa possessed the most powerful antioxidant potential evaluated by DPPH and ABTS assays among 65 edible flowers (Kim et al 2016;Zheng et al 2018). Moreover, there have been few investigations referring to the antioxidant activities of S. komarovii, A. princeps, and R. rugosa (Carvalho et al 2011;Kim et al 2018;Lee et al 2012;Youwei and Yonghong 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the successful tolerance in hostile conditions, for example, salinity, UV radiation, and extreme temperature, HP is believed to allow valuable secondary metabolites including polyphenol, carotenoid, and vitamins to cope with those stress-overwhelmed environments (Jdey et al 2017). It is also suggested that HP may offer a great unexplored source of bioactivity for the medicine or cosmetic development with economic benefit (Kim et al 2016). In our present study, 22 HPs harvested along the coast of South Korea were screened and evaluated whether to provide antioxidant, anti-aging, as well as whitening potentials for cosmeceutical applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tyrosinase expression and activation play an essential role in melanin production. Although melanin protects the skin against UV injury under normal physiological conditions, abnormal pigmentation such as freckles and age spots often causes serious skin problems and esthetic issues 25 . A few known natural tyrosinase inhibitors of melanin synthesis including adenosine, arbutin, niacinamide, and kojic acid are currently used as cosmetic and medicinal ingredients in preparations applied for the treatment of hyperpigmentation.…”
Section: Discussionmentioning
confidence: 99%